2015
DOI: 10.1002/pmic.201500167
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of cerebrospinal fluid in California sea lions (Zalophus californianus) with domoic acid toxicosis identifies proteins associated with neurodegeneration

Abstract: Proteomic studies including marine mammals are rare, largely due to the lack of fully sequenced genomes. This has hampered the application of these techniques toward biomarker discovery efforts for monitoring of health and disease in these animals. We conducted a pilot label-free LC-MS/MS study to profile and compare the cerebrospinal fluid from California sea lions with domoic acid toxicosis (DAT) and without DAT. Across 11 samples, a total of 206 proteins were identified (FDR<0.1) using a composite mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…In addition, recent evidence suggests other changes, perhaps indicative of early AD, can be found in other sea mammals. Investigating the stranding and death of sea-lions suffering from domoic acid toxicosis due to blue-green algae, it has been reported that CSF from these animals shows evidence of changes indicative of neurodegeneration [56]. Using untargeted mass spectrometry proteomics methods, Neely et al found an excess of multiple complement proteins and gelsolin, proteins we and others have reported to be associated with AD [57,58].…”
Section: Do Cetaceans or Other Diving Animals Have Dementia?mentioning
confidence: 94%
“…In addition, recent evidence suggests other changes, perhaps indicative of early AD, can be found in other sea mammals. Investigating the stranding and death of sea-lions suffering from domoic acid toxicosis due to blue-green algae, it has been reported that CSF from these animals shows evidence of changes indicative of neurodegeneration [56]. Using untargeted mass spectrometry proteomics methods, Neely et al found an excess of multiple complement proteins and gelsolin, proteins we and others have reported to be associated with AD [57,58].…”
Section: Do Cetaceans or Other Diving Animals Have Dementia?mentioning
confidence: 94%
“…Despite focusing on two different viral genera, such results suggest both similarities and differences in how bats and humans may respond to CoV infection. More generally, the list of such candidate biomarkers identified here can be used to create accurate, sensitive, quantitative, and bat-specific parallel reaction monitoring mass spectrometry-based protein assays (Neely et al, 2013, 2015). Such assays could facilitate more thorough investigations into bat immune response to CoV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other marine mammals, a previous study of kidney diseases in wild animals identified a total of 2694 proteins in the urine of 19 California sea lions ( Zalophus californianus ) 21 . However, only 206 proteins were identified from the cerebrospinal fluid of 11 California sea lions 22 . Conversely, two previous studies of plasma samples from bottlenose dolphins (T ursiops truncates ) only identified 58 and 196 unique proteins, respectively 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%